“At Risk” Adolescent Boys’ Engagement With an Employability Intervention: A Qualitative Exploration - Carmichael-Murphy, Parise; Demkowicz, Ola; Humphrey, Neil (Frontiers in Education, 2022)
The individualization of Not in Education, Employment, or Training (NEET) status has contributed to a culture of blame that frames adolescent boys’ transition into employment and economic independence. Drawing on Urie Bronfenbrenner’s ecological systems theory, we explored how adolescent boys categorized as “at risk” of becoming NEET engage with a school-based work-readiness intervention. We interviewed five adolescent boys aged 13–14 years about their experiences of the intervention. Using reflexive thematic analysis, three main themes were constructed: (1) challenge mediated by choice; (2) access to supportive relationships; and (3) recognizing personal development. The findings illustrate the interrelatedness of adolescent boys’ engagement with, and within, their environment; findings support a push to consider engagement as an ecological concept. We end with considerations for more ecologically sensitive approaches to work-related intervention and the assessment of adolescent boys’ “at risk” status.